PENGUASAAN HARTA WARISAN OLEH SEBAGIAN AHLI WARIS DI DESA ALUE BARO KECAMATAN MEUKEK ACEH SELATAN MENURUT PERSPEKTIF KOMPILASI HUKUM ISLAM - Fauzi, Fakhrul; Moulia, Nouvan (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
In Alue Baro village, Meukek subdistrict, South Aceh Regency, a case of inheritance issues was found, where some heirs unilaterally controlled the inheritance left by their parents and did not give shares to other heirs. In this case, the position is occupied by a substitute heir, who is the son of the heir who should have received the inheritance from the testator. His father's position to receive the inheritance was transferred to the testator's grandson because the original heir had passed away before the testator. This substitute heir is often referred to as